substitution method

posted by .

-3x+y=-5 x+2y=0

Your equations:
-3x + y = -5
x + 2y = 0

Let's solve the second equation for x:
x = -2y

Now let's substitute -2y for x in the first equation to solve for y:
-3(-2y) + y = -5
6y + y = -5
7y = -5
y = -5/7

Now let's substitute -5/7 for y in the second equation to solve for x:
x + 2(-5/7) = 0
x + -10/7 = 0
x = 10/7

Check these values with the original equations. It always helps to check your work!

I hope this will help.

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. Algebra 2345678!!

    Solve the system of equations using the Addition method. 2a + 3b = -1 3a + 5b = -2 The addition method tells you to find common multiples of a coefficient, then add the equations together to eliminate a variable. If you multiply the …
  2. Substitution Method-Plz help

    Use the Substitution method to solve the system of equations. x + y = -4 x - y = 2 solve for x in the second equation. x= y+2 Put that in for x in the first equation: x+y=-4 (y+2) + y = -4 solve for y. Then, x= y+2 i don't get it.How …
  3. ALGEBRA 1!PLZ HELP!

    Use the Substitution method to solve the system of equations. y - 2x = -5 3y - x = 5 Solve the first equation for y. y = 2x-5 Substitute that for y in the second equation and solve for x. Then use the value of x to substitute back …
  4. How do I do this.?(Math.)

    Use the Substitution method to solve the system of equations. y - 2x = -5 3y - x = 5 Solve one of the equations for x or y. Let's solve the first one for y: y - 2x = -5 y = 2x - 5 Now let's substitute 2x - 5 for y in the second equation …
  5. correction of math

    can someone correct this for me please. Directions: Solve the system by substitution. x + y = 12 y = 2x this is what i did: in the first equation i substituted y for what i have in the second equation so now it looks like this: x +2x …
  6. substitution method

    -x-4y=-14 2x=y+1 Let's look at your two equations. -x - 4y = -14 2x = y + 1 Let's solve the second equation for y: y = 2x - 1 Now let's substitute (2x - 1) for y in the first equation: -x - 4(2x - 1) = -14 -x - 8x + 4 = -14 -9x + 4 …
  7. Alg-Substitution (check plz)

    k well i had to use substitution to find the point of intersection for these 2 equations x-y=10 3x+y=11 i chose to substitute y in the first equation my final answer was (-1/2 , 5) can someone clarify this, and if it's wrong, where'd …
  8. algebra

    5x-2y=-5 y-5x=3 substitution Substitute 5x +3 for y in the first equation, then solve it for x. Substitute 5x +3 for y in the first equation, then solve it for x. When I subsitute 5x+3 into the equation I get x=1/5 and y=2 is this …
  9. Algebra

    Please help to find x, y 1. 8x-y=17 6x+y=11 2. 5x-2y=17 2x+3y=3 Question no.1 8x-y=17 6x+y=11 (adding the equation) __________ (-y and +y will be 0) 14x =28 Taking variables to one side x=28 __ 14 14*2=28 therefore x=2 substitute this …
  10. Algebra 1

    What is an equation of a line perpendicular to the line with equation y = 1 - 3x a.y=-3x + 5 b. y=3x + 5 c.y=-1/3x + 5 d. y=1/3x + 5 To solve the linear system below, which substitution of unkowns is proper ?

More Similar Questions